2016
DOI: 10.1002/ange.201606750
|View full text |Cite
|
Sign up to set email alerts
|

Independent Control of Elastomer Properties through Stereocontrolled Synthesis

Abstract: In most synthetic elastomers,c hanging the physical properties by monomer choice also results in ac hange to the crystallinity of the material, which manifests through alteration of its mechanicalperformance.Using organocatalyzed stereospecific additions of thiols to activated alkynes,h igh-molarmass elastomers were isolated via step-growth polymerization. The resulting controllable double-bond stereochemistry defines the crystallinity and the concomitant mechanical properties as well as enabling the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…DSC revealed a clear influence of cis-alkene content on thermal transitions as depicted in the thermograms in Fig. 5d-f, which is in line with reports by Buchard 39 and Dove and Becker 3,40 . In addition to small variations of glass transition temperatures (Tg), striking differences in crystalline behavior were observed.…”
supporting
confidence: 90%
“…DSC revealed a clear influence of cis-alkene content on thermal transitions as depicted in the thermograms in Fig. 5d-f, which is in line with reports by Buchard 39 and Dove and Becker 3,40 . In addition to small variations of glass transition temperatures (Tg), striking differences in crystalline behavior were observed.…”
supporting
confidence: 90%
“…This behavior is consistent with a more elastic material that is expected from the interruption of crystallinity through the introduction of ester groups into the main chain that disrupt chain packing and increase chain mobility. These findings were confirmed via differential scanning calorimetry (DSC) which showed that increasing %cis without altered succinate content increased the glass transition temperature in line with results from our previous work 5,29 . Significantly, the materials exhibit high thermal stability and the onset of degradation temperatures exceeds 350°C.…”
supporting
confidence: 88%
“…Until now, no synthetic resorbable elastomer or elastomer-like polymer system have afforded independent control of mechanical properties and degradation de novo 2 . We recently reported the first metal-free, stereocontrolled step-growth polymerization via a nucleophilic thiol-yne addition which yielded a series of thermally-processable elastomers in which the mechanical properties were controlled by the double bond stereochemistry 5,29 . The double bond stereochemistry (% cis) in each thiol-yne step growth polymer was tuned based on solvent polarity and organic base which is able to preferentially direct the thiol addition to the cis stereochemistry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Becker and Dove reported an organocatalytic stereocontrolled synthesis of unsaturated polyesters, resulting in a tunable cis/trans ratio, crystallinity, and mechanical properties. 14 Postpolymerization catalysis was also exploited to isomerize poly(propylene maleate) into poly(propylene fumarate) toward 3D printing and medical applications. 15−17 The ability to drastically change polymer properties through cis/trans isomerization, e.g.…”
mentioning
confidence: 99%